If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2y+3)=6
We move all terms to the left:
6(2y+3)-(6)=0
We multiply parentheses
12y+18-6=0
We add all the numbers together, and all the variables
12y+12=0
We move all terms containing y to the left, all other terms to the right
12y=-12
y=-12/12
y=-1
| 8(8-7p)=2(2p+2 | | 1/2x+1/3x+10=x | | 6+8f;f=4 | | (1.50+0.60)x=13.50 | | 1/2(-2x+10)+9=10(x+1)+5 | | 51x-1+7x+1=130 | | 3x+5÷6=2x-5 | | 4i-12-;i=4 | | -5=-7v+5(v-3) | | 6000x=15 | | 0.7x+0.9=0.9x-0.1 | | 1,250+10x=2500 | | (5/2)t-1=3+(3/2)t | | 8x-(3x-10)=34 | | 60x=0.15 | | 236784+x34876587648623+4943659+69=x | | -2(v+9)=4v-30 | | 4(z-5)+25=29 | | 16^1.25=x | | 2x+40x=74 | | 2(-4m+7)=-1-3m | | -7y+12=8(y+9) | | 2x+45=x+29 | | 18=-7(8k+2)-8(k+4) | | 2+6x=1–x | | 4r+1=12 | | 2x-6=7x-49 | | 2x(x+3)=x=23 | | -10k=-60 | | x-44-x3=6 | | 186t+16=1132 | | 240+0.25=180+0.40m |